(untitled) (Theatrum historiae, 2016)
In this study the author specifically summarises Czech research on nobility in relation to the Habsburg Monarchy during the 19th Century. She demonstrates that the nobility did not comprise a monolithic, internally undifferentiated unit, because its lifestyle was still regulated by the specific provisions of the aristocratic hierarchy, which did not always have the nature of a standard legal norm. It was above all the nobility who clung to its observances and enclosed itself in an increasingly tighter, though not hermetically sealed, individual group of persons. In terms of their number, they represented a mere fraction of the entire society, but their significance could not be entirely ignored. Meanwhile, in the traditional area of aristocratic influence its impact was gradually fading. During the 19th Century this process probably progressed most rapidly in the army and specifically amongst the senior officers. A more complex situation arose at a higher level of the Catholic hierarchy, whereas this trend manifested to its least extent within the diplomatic service. Meanwhile the nobility that did not have any direct ties to the Imperial Court was gradually losing-out. In the mid-19th Century the nobility lost both their rights and their obligations as landed lords. On the other hand, usually nothing would prevent them from participating in a modern business. Not everybody belonging to this social layer, however, had both the necessary ability and/or the desire to do so.